Analysis Of Audit Procedures On Fixed Assets At PT. Idt By Kap Djoko Soerjadi - Rheza Ernowo Wicaksono; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Fixed asset audit is an important procedure in ensuring the accuracy and reliability of information about fixed assets that have been reported in the financial statements. The value of fixed assets decreases in accordance with its useful life or what is called depreciation. Depreciation will affect the book value of fixed assets presented in the statement of financial position and also become a deduction component of profit before tax in the income statement. Therefore, an audit of fixed assets is important to be carried out by a public accounting firm that is conducting an audit. This study aims to determine the audit procedures on fixed assets carried out by KAP Djoko Soerjadi in auditing one of its clients, namely PT IDT which is engaged in ship rental and agency services. The research method used is a qualitative research method with a descriptive analysis approach, through collecting, classifying, compiling, and presenting and analyzing data obtained from PT IDT. Audit procedures that have been carried out by KAP Djoko Soerjadi are in accordance with applicable audit theories and standards.